Serum Hepatitis C virus and hepatitis B surface antigenaemia patients with acute icteric hepatitis (2002)
Acute hepatitis is common in Nigeria and hepatitis B virus (HBV) infection has been a major aetiological factor. However, the role of Hepatitis C virus (HCV) infection is yet undetermined. Forty-five consecutive Nigerian patients with Acute Icteric hepatitis (AIH) attending the medical clinic of the University College Hospital, Ibadan, Nigeria and 45 health adult Nigerians (controls) were studied for evidence of infection with both viruses. Questionnaire on risk procedures which predispose to acquisition of both HBV and HCV infections were administered to the patients. Blood samples were collected from all the subjects and tested for antibody to HCB (Anti-HCV) and Hepatitis B surface Antigen (HBsAg) using the second generation enzyme linked Immunoassay (Monosila-R, Sansofi, Pasteur;France). Anit-HCV was detected in 21(47%) and 17 (38%) of the patients and controls respectively. The corresponding prevalences of HBsAg were 38(84%) and 11(24%), p<0.001. Hepatitis B virus infection was found to occur more than the controls. Combined HBV and HCV infection occured more frequently among the patients(42.1%) than in the control (11%)(;<0.001). Although there was no significant difference in the HCV infection between the two groups, isolated HCV infection is commoner in the control than in the patients with AIH, (p<0.001). Similarly, single HCV infection is commoner than lone HBV infection among the control, p<0.05. In summary, this study shows that while both HBV and HCV infections are common in Nigeria, AIH may be more associated with HBV than HCV in the country.